SNP–SNP Interactions of Surfactant Protein Genes in Persistent Respiratory Morbidity Susceptibility in Previously Healthy Children - Gandhi, Chintan K.; Thomas, Neal J.; Meixia, Ye; Spear, Debbie; Fu, Chenqi; Zhou, Shouhao; Wu, Rongling; Keim, Garrett; Yehya, Nadir; Floros, Joanna (Frontiers in Genetics, 2022)
We studied associations of persistent respiratory morbidity (PRM) at 6 and 12 months after acute respiratory failure (ARF) in previously healthy children with single nucleotide polymorphisms (SNPs) of Surfactant protein (SP) genes. Of the 250 enrolled subjects, 155 and 127 were followed at 6 and 12 months after an ARF episode, respectively. Logistic regression analysis and SNP-SNP interaction models were used. We found: a) in the multivariate analysis, increased risk at 6 and 12 months was associated with rs1124_A and rs4715_A of SFTPC, respectively; b) in a single SNP model, increased and decreased risk of PRM at both time points was associated with rs1124 of SFTPC and rs721917 of SFTPD, respectively; increased risk at 6 months was associated with rs1130866 of SFTPB and rs4715 of SFTPC; and increased and decreased risk at 12 months was associated with rs17886395 of SFTPA2 and rs2243639 of SFTPD, respectively; c) in a two-SNP model, PRM susceptibility at both time points was associated with a number of intergenic interactions between SNPs of the studied SP genes. Increased risk at 12 months was associated with one intragenic (rs1965708 and rs113645 of SFTPA2) interaction; d) in a three-SNP model, decreased and increased risk at 6 and 12 months, respectively, was associated with an interaction among rs1130866 of SFTPB, rs721917 of SFTPD and rs1059046 of SFTPA2. Decreased risk at 6 months was associated with an interaction among the same SNPs of SFTPB and SFTPD and the rs1136450 of SFTPA1. The findings revealed that SNPs of all SFTPs appear to play a role in long-term outcomes of ARF survivors and may serve as markers for disease susceptibility.